2011
DOI: 10.1007/s11914-011-0068-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Smoke Carcinogens on Bone

Abstract: The greatest cause of preventable morbidity and mortality is smoking, and one of the often-underappreciated effects of smoking is profound bone loss. The existing clinical paradigm for smoking is that there is a low turnover osteoporosis. This review highlights findings from recent clinical trials and animal research demonstrating either support or conflict with the existing paradigm. Clinically, it is noted that markers of bone formation are often normal in smokers; these clinical findings conflict with well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 37 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Yan and colleagues () have reported a negative influence of smoking on BMD. Although our sample consisted of heavy smokers (on average 30.6 pack‐years), we were unable to find a negative correlation between smoking and BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Yan and colleagues () have reported a negative influence of smoking on BMD. Although our sample consisted of heavy smokers (on average 30.6 pack‐years), we were unable to find a negative correlation between smoking and BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient deficiency impairs fetal bone development. 17,26,27) In a prospective birth cohort study that aimed to evaluate the effect of parental smoking during pregnancy on the bone mass of 7,121 children at 10 years of age, maternal smoking was associated with an increased risk of total body less head, spine BMC, bone area, and BMD in girls; however, the relationship was not significant for boys. 25 large birth cohort study of 6,718 children in Northern Finland showed that MSDP was directly associated with an increased risk of in-hospital-treated fractures at pre-school age (RR, 1.83fold; 95% CI, 1.06-3.02; P=0.022).…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, tobacco smoking has been associated with increased intervertebral disc degeneration, decreased bone mineral density and reduced microstructural integrity of cerebral white matter. 9,11,31 Furthermore, nicotine treatment results in stenosis of and a decrease in the number of vascular bulbs, enlargement of vascular endothelial cells, and reduced blood flow.…”
Section: Discussionmentioning
confidence: 99%